Microwave processing impact on the phytochemicals of sorghum seeds as food ingredient. Issue 5 (18th March 2019) - Hassan, Sadia; Ahmad, Nazir; Ahmad, Tanvir; Imran, Muhammad; Xu, Changmou; Khan, Muhammad Kamran
Abstract: Nowadays, to preserve or modify the phytochemical constituents of processed food products for improving their nutritional profile, application of microwave processing has achieved special attention. Microwave processing parameters were optimized to improve the phytochemical profile of sorghum seeds through their sprouting. In this work, overall impact of microwave processing on different phytochemical constituents (alkaloid, saponin, phytate, and sterols), antioxidant activities (DPPH, FRAP, and ORAC assay), phenolic compounds (total phenolic contents, total flavonoid contents, gallic acid, ferulic acid, catechin, quercetin, tannin) as well as in vitro protein digestibility occurring during sorghum grain germination was assessed. Among different treatment levels, microwave power level of 700 W for 15 s gave the best results for the studied parameters. The microwave‐processed sorghum sprouts with improved phytochemical composition may provide effective raw material to formulate low‐cost and high‐protein weaning/functional foods. Practical applications: In developing countries, use of locally available food resources for formulating weaning/functional foods is an enormous task. Therefore, sorghum seeds could be utilized in the development of low cost, sorghum‐based high‐protein weaning/functional foods. The present work showed that microwave processing of sorghum seed could impart improvement in their composition regarding phenolic profile, antioxidant activity, and in vitro protein digestibility of sorghum sprouts. Thus, as compared to unprocessed germinated seeds, microwave‐processed sorghum sprouts having high nutritional profile could be a preferable ingredient to develop weaning/functional foods.